Motivasi Belajar Praktik Tari Tradisional dalam Jaringan - Sangadah, Miftahus (Program Studi Pendidikan Tari FBS UNJ, 2021)
Miftahus Sangadah. 2021. Learning Motivation in Distance Learning for Traditional Dance Practices. Thesis, Dance Education. Faculty of Language and Art. The State University of Jakarta. The results of the Kolmogorov-Smirnov test analysis of the residual value of 116 students of 0.767 are greater than α = 0.05, so it can be concluded that the research variables used are normally distributed. The correlation test between the five indicators shows that they are interrelated with a significance value of 0.000. The indicator with the highest correlation value is interest and sharpness of attention in learning with independent indicators in learning of 0.615 **. The indicator with the lowest correlation value is the indicator of resilience in facing difficulties with the indicator of achievement in learning 0.256 **. Distance learning which is applied in the Dance Education Study Program of the State University of Jakarta is online learning which is carried out using learning applications and social networks. The influence of learning motivation in distance learning on traditional dance practice courses at the Jakarta State University Dance Education Study Program is in the medium category with a percentage of 40.52%.